The Evolution of Meaning: The Causes of the Evolution of the Meaning of Words, The Restriction and Extension of Meaning (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article is about the causes of the evolution of the meaning of words, the restriction and extension of meaning. Lexicology is the branch of linguistics that analyzes the lexicon of a specific language. A word is the smallest meaningful unit of a language that can stand on its own, and is made up of small components called morphemes and even smaller elements known as phonemes, or distinguishing sounds. Lexicology examines every feature of a word – including formation, spelling, origin, usage, and definition.